Math, asked by kavitachandak83, 3 months ago

please help me doing this maths sum​

Attachments:

Answers

Answered by mathdude500
3

\large\underline{\sf{Solution-}}

Consider,

\rm :\longmapsto\: {\bigg(\dfrac{ {x}^{ {a}^{2}  +  {b}^{2} } }{ {x}^{ - ab} } \bigg) }^{a - b}

\red{\bigg \{ \because \:  {x}^{m}  \div  {x}^{n}  =  {x}^{m - n} \bigg \}}

\rm \:  =  \:  \:  {\bigg( {x}^{ {a}^{2}  +  {b}^{2} + ab } \bigg) }^{a - b}

\rm \:  =  \:  \:  {\bigg({x}^{({a}^{2}  +  {b}^{2} + ab)(a - b)} \bigg) }

\rm \:  =  \:  \:  {x}^{ {a}^{3}  -  {b}^{3} }

\bf :\longmapsto\: {\bigg(\dfrac{ {x}^{ {a}^{2}  +  {b}^{2} } }{ {x}^{ - ab} } \bigg) }^{a - b}  =  {x}^{ {a}^{3}  -  {b}^{3} }

Consider,

\rm :\longmapsto\: {\bigg(\dfrac{ {x}^{ {b}^{2}  +  {c}^{2} } }{ {x}^{ - bc} } \bigg) }^{b - c}

\rm \:  =  \:  \:  {\bigg( {x}^{ {b}^{2}  +  {c}^{2} + bc } \bigg) }^{b - c}

\red{\bigg \{ \because \:  {x}^{m}  \div  {x}^{n}  =  {x}^{m - n} \bigg \}}

\rm \:  =  \:  \:  {\bigg({x}^{({b}^{2}  +  {c}^{2} + bc)(b - c)} \bigg) }

\rm \:  =  \:  \:  {x}^{ {b}^{3}  -  {c}^{3} }

\bf :\longmapsto\: {\bigg(\dfrac{ {x}^{ {b}^{2}  +  {c}^{2} } }{ {x}^{ - bc} } \bigg) }^{b - c}  =  {x}^{ {b}^{3}  -  {c}^{3} }

Consider,

\rm :\longmapsto\: {\bigg(\dfrac{ {x}^{ {c}^{2}  +  {a}^{2} } }{ {x}^{ - ca} } \bigg) }^{c - a}

\rm \:  =  \:  \:  {\bigg( {x}^{ {c}^{2}  +  {a}^{2} + ac } \bigg) }^{c - a}

\red{\bigg \{ \because \:  {x}^{m}  \div  {x}^{n}  =  {x}^{m - n} \bigg \}}

\rm \:  =  \:  \:  {\bigg({x}^{({c}^{2}  +  {a}^{2} + ac)(c - a)} \bigg) }

\rm \:  =  \:  \:  {x}^{ {c}^{3}  -  {a}^{3} }

\bf :\longmapsto\: {\bigg(\dfrac{ {x}^{ {c}^{2}  +  {a}^{2} } }{ {x}^{ - ca} } \bigg) }^{c - a}  =  {x}^{ {c}^{3}  -  {a}^{3} }

Now, Consider

 \red{\rm :\longmapsto\:{\bigg(\dfrac{ {x}^{ {a}^{2} +  {b}^{2}  } }{ {x}^{ - ab} } \bigg) }^{a - b}{\bigg(\dfrac{ {x}^{ {b}^{2} +  {c}^{2}  } }{ {x}^{ - bc} } \bigg) }^{b - c}{\bigg(\dfrac{ {x}^{ {c}^{2} +  {a}^{2}  } }{ {x}^{ - ca} } \bigg) }^{c - a}}

\rm \:  =  \:  \: {x}^{ {a}^{3}  -  {b}^{3} } \:  \times \:  {x}^{ {b}^{3}  -  {c}^{3} }  \: \times  \:  {x}^{ {c}^{3}  -  {a}^{3} }

\rm \:  =  \:  \: {x}^{ {a}^{3}  -  {b}^{3} +  {b}^{3}  -  {c}^{3}   +  {c}^{3}  -  {a}^{3} } \:

\red{\bigg \{ \because \:  {x}^{m}  \times   {x}^{n}  =  {x}^{m + n} \bigg \}}

\rm \:  =  \:  \: \:   {x}^{0}

\rm \:  =  \:  \: \:   1

Hence, Proved

More Identities to know:

(a + b)² = a² + 2ab + b²

(a - b)² = a² - 2ab + b²

a² - b² = (a + b)(a - b)

(a + b)² = (a - b)² + 4ab

(a - b)² = (a + b)² - 4ab

(a + b)² + (a - b)² = 2(a² + b²)

(a + b)³ = a³ + b³ + 3ab(a + b)

(a - b)³ = a³ - b³ - 3ab(a - b)

Similar questions